THE EFFECT OF FINANCIAL LITERACY, FINANCIAL BEHAVIOR, DIGITAL PAYMENT, AND THE ABILITY TO PREPARE FINANCIAL REPORTS ON THE PERFORMANCE OF MSMES IN LHOKSEUMAWE CITY - Muhammad Yusra; Nur Afni Yunita; Sri Mulyati; Rany Gesta Putri Rais; Mardiaton (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to determine the influence of Financial Literacy, Financial Behavior, Digital Payment, and the Ability to Prepare Financial Reports on the Performance of MSMEs in Lhokseumawe City for the period 2019-2023. The population in this study were MSMEs registered with the Lhokseumawe City Trade, Industry, Cooperatives, and SMEs Office, with a sample of 100 MSMEs selected using Purposive Sampling techniques, namely sample selection based on certain criteria. The data collection technique used in this study was a questionnaire. Data analysis was carried out using descriptive percentage analysis, instrument testing, classical assumption testing, and hypothesis testing. Instrument testing consisted of validity and reliability tests, while classical assumption testing included normality tests, multicollinearity tests, and heteroscedasticity tests. Hypothesis testing in this study was carried out using multiple linear regression analysis, partial tests (t-tests), and coefficient of determination (R²) tests. The results of the study indicate that financial literacy, financial behavior, digital payments, and the ability to prepare financial reports partially have a positive and significant effect on the performance of MSMEs in Lhokseumawe City. This suggests that the better the financial understanding, financial habits, adoption of digital payment systems, and financial reporting skills, the better the performance of MSMEs in the area.